1996
DOI: 10.1177/014107689608901107
|View full text |Cite
|
Sign up to set email alerts
|

The Cholesterol-Raising Factor from Coffee Beans

Abstract: Coffee beans and some types of coffee brew-not the regular types of coffee prepared with a paper filter or with soluble coffee granules-contain the diterpenes cafestol and kahweol. Cafestol and kahweol raise the serum concentration of cholesterol and triglycerides in humans, and they also appear mildly to affect the integrity of liver cells. Both effects are transient after withdrawal of the diterpenes, and it is as yet unsure whether these effects are associated. Patients at increased risk of heart disease wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0
5

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 44 publications
3
61
0
5
Order By: Relevance
“…Could a lowering of Lp(a) levels with consumption of coffee diterpenes confer any health bene®t? In a metaanalysis of eleven trials with preparations rich in cafestol and kahweol, we found that each 10 mg of cafestol ingested per day raises serum total cholesterol by 0.15 mmol/L, which was mostly due to an increase in LDL cholesterol (Urgert & Katan, 1997b). The hypercholesterolemic potency of coffee diterpenes thus overrules their potential bene®cial impact on Lp(a) levels.…”
Section: Discussionmentioning
confidence: 92%
“…Could a lowering of Lp(a) levels with consumption of coffee diterpenes confer any health bene®t? In a metaanalysis of eleven trials with preparations rich in cafestol and kahweol, we found that each 10 mg of cafestol ingested per day raises serum total cholesterol by 0.15 mmol/L, which was mostly due to an increase in LDL cholesterol (Urgert & Katan, 1997b). The hypercholesterolemic potency of coffee diterpenes thus overrules their potential bene®cial impact on Lp(a) levels.…”
Section: Discussionmentioning
confidence: 92%
“…Uma meta--análise de 14 estudos sobre a associação entre o consumo de café sob diferentes métodos de preparo, e o perfil lipídico sérico de indivíduos verificou uma relação causal entre ingestão de café fervido e aumento de colesterol sérico 14 . Dusseldorp et al 12 , estudando 64 pacientes com um consumo diário de 6 xícaras de 150mL, observaram após 14 semanas um aumento de 16mg/dL de colesterol total e LDL-C. Urger & Katan 5 relataram um aumento no colesterol total de 5mg/dL com a ingestão de 10mg de cafestol, e de 0,9mg/dL com a ingestão de 10mg de kahweol. Por outro lado, outros estudos não encontraram alterações no perfil lipídico sérico 15,33,34 .…”
Section: I S C U S S ã Ounclassified
“…2 We estimated that each 10 mg of cafestol ingested per day raises serum cholesterol levels by 0.13 mmol/L. 3 In humans, Ϸ80% of the rise in total cholesterol is accounted for by LDL cholesterol, and the rest is due to a rise in VLDL cholesterol. 4 The mechanism by which coffee diterpenes influence lipid metabolism is largely unknown.…”
mentioning
confidence: 99%